KEDUDUKAN HUKUM CRYPTOCURRENCY DI INDONESIA: ANTARA INVESTASI SERTA ALAT PEMBAYARAN - Purwanto, Eko (Jurnal HUKUM BISNIS, 2025)
Cryptocurrency is recognized as a commodity that can be traded on a futures exchange, but is not recognized as legal tender under Law Number 7 of 2011 concerning Currency. Although it attracts the attention of many investors as an alternative investment, the legal status and regulations governing its use are still debated. This study aims to analyze the legal position of cryptocurrency in the Indonesian positive legal system, identify relevant regulations, and evaluate legal protection for investors. The research method used is normative legal research with a statutory and conceptual approach. The results of the study show that although there is legal protection for investors, significant legal risks remain, including regulatory uncertainty, potential fraud, and market volatility. Therefore, it is necessary to strengthen regulations and increase supervision to protect investors and maintain the integrity of the cryptocurrency market in Indonesia. Keywords: Cryptocurrency, Investment, Regulation, Legal Protection